Factoring in Minecraft - Butler, Kenneth L (Ohio Journal of School Mathematics, 2022)
In this paper, the author describes a method for using MineCraft as a manipulative for factoring composite numbers and quadratic equations. These concepts are extended to an investigation of perfect square trinomials, completing the square, and Pythagorean triplets.